Cogeneration : technologies, optimisation and implementation - Frangopoulos, Christos A. (IET energy engineering series, 2017)
"Cogeneration, also called combined heat and power (CHP), refers to the use of a power station to deliver two or more useful forms of energy, for example, to generate electricity and heat at the same time. All conventional, fuel-based plants generate heat as by-product, which is often carried away and wasted. Cogeneration captures part of this heat for delivery to consumers and is thus a thermodynamically efficient use of fuel, and contributes to reduction of carbon emissions. This book provides an integrated treatment of cogeneration, including a tour of the available technologies and their features, and how these systems can be analysed and optimised. Topics covered include benefits of cogeneration; cogeneration technologies; electrical engineering aspects; applications of cogeneration; fuels for cogeneration systems; thermodynamic analysis; environmental impacts of cogeneration; reliability and availability; economic analysis of cogeneration systems; regulatory and legal frameworks; selection, integration and operation of cogeneration systems; simulation and optimisation; synthesis, design and operation; examples of cogeneration projects; research and development of cogeneration; summary and conclusions. This book is intended for instructors and students at advanced undergraduate as well as graduate level, for professional engineers who design, build and operate cogeneration systems, and for researchers on analysis and optimisation of energy systems."--Provided by publisher.